Comparative follow up of patients with implanted cardioverter-defibrillators after induction of sustained monomorphic ventricular tachycardias or ventricular fibrillation by programmed stimulation. Issue 6 (1st June 2003) - Meyborg, M; Mura, R; Tiefenbacher, C; Becker, R; Michaelsen, J; Niroomand, F
Abstract : Objective: To investigate the prognostic value of induced monomorphic ventricular tachycardia (VT) and ventricular flutter or fibrillation (VF) during programmed electrical stimulation in patients with a high risk for sudden arrhythmogenic cardiac death. Design: Prospective cohort study. Patients: 102 patients at high risk for arrhythmogenic sudden cardiac death who received an automated implantable cardioverter-defibrillator (AICD) were evaluated. 56 patients received the AICD for primary prevention and 46 for secondary prevention. 58 patients had induction of a monomorphic VT (VT group) and 44 had induction of a polymorphic VT, ventricular flutter, or ventricular fibrillation (VF group) during programmed electrical stimulation. Average follow up was 20 months in both groups. Main outcome measures: Appropriate AICD protocol. Results: In patients who received the AICD for primary prevention, 16 of 32 patients in the VT group, compared with only four of 24 patients in the VF group, received an appropriate AICD protocol (p = 0.02). In the entire study population, 479 appropriate AICD protocols were recorded in 28 (48%) patients in the VT group and 28 appropriate protocols in 11 (25%) patients in the VF group. Cumulative Kaplan-Meier event-free survival curves were significantly different (p = 0.02). Conclusion: Induction of VF during programmed electrical stimulation is of no prognostic value even in high risk patients without previously documented ventricular fibrillation.